Effects of drinking water fructo-oligosaccharide supplementation on broiler chicken growth performance, blood glucose level, white blood cell count, carcass yield, meat quality, and cecal microbiota - Siriporn Namted; Phiangchai Chailaor; Chaiyapoom Bunchasak (Poultry Science)
This study investigated the effects of fructo-oligosaccharides (FOS) supplementation on the growth performance, blood glucose level, white blood cell count, carcass yield, meat quality, and cecal microbiota of Ross 308 broiler chickens. A completely randomized design was employed; FOS was supplemented in the drinking water at concentrations of 0 %, 0.25 %, and 0.50 %. From 11 to 24 d of age, 0.25 % FOS supplementation significantly increased feed intake (FI), while feed cost per gain (FCG) was significantly reduced at 0.50 % FOS (P < 0.05). During the overall period (1–36 d of age), FOS supplementation significantly improved the European Production Efficiency Factor (EPEF) (P < 0.01), and slowed down the reduction in blood glucose levels after the re-feeding period (2, 3, 4, and 5 h) (P < 0.01). Furthermore, FOS supplementation decreased the heterophil/lymphocyte (H:L) ratio (P < 0.05). However, it had no significant effect on breast meat yield or abdominal fat, but 0.50 % FOS supplementation tended to increase the percentage of cecal weight (P = 0.08). Supplementation with FOS (0.25 % and 0.50 %) significantly reduced breast meat cooking loss (P < 0.05). Regarding cecal microbiota, the FOS-supplemented groups showed increased abundances of Lactobacillaceae and Acidaminococcaceae, whereas the abundances of Lachnospiraceae and Barnesiellaceae were reduced (P < 0.05). In conclusion, drinking water FOS supplementation had a beneficial effect on the overall productive performance and cooking loss of broiler chickens via stress reduction, which may involve an improvement in the gut microbiota.